Simultaneous scheduling and binding for resource usage and interconnect complexity reduction in high-level synthesis - Cong Hao; Jian-Mo Ni; Hui-Tong Wang; Yoshimura, Takeshi (Proceedings (International Conference on ASIC), 2015)
This paper proposes a simultaneous scheduling and binding approach for resource and interconnect reduction in high-level synthesis. The scheme incorporates the operation scheduling into functional unit (FU) and register binding, targeting the reduction of both resource and interconnect reduction. A simplified weighted and ordered compatibility graph (SWOCG) based binding algorithm is also proposed and runs tens of times faster than the WOCG based binding algorithm. The experimental results show that our proposal achieves 4% to 15% reduction in resource usage and interconnect reduction, and also runs 5X faster compared to previous works.